Impacto de la apertura comercial de México y de su integración en bloques comerciales en el mercado mundial del limón - Guajardo Quiroga, Ramón G.; Villezca Becerra, Pedro A. (El Colegio de México, A.C., 2004)
This paper studies the liberalization of the Mexican lemon market in a world perspective using a spatial equilibrium model with endogenous prices. Several scenarios were designed related to the lemon market involving the countries that integrate NAFTA, and MEUFTA, and the removal of commercial barriers related to this fruit. The potential impact of eliminating tariffs on commercial flows, prices, and welfare are estimated. The results suggest that Mexico will benefit from NAFTA, and MEUFTA, as well as, the removal of commercial barriers in the world lemon market.